Participatory implementation within climate change related policies in urbanized area of Indonesia - Utia Suarma; Dyah Rahmawati Hizbaron; Sudibyakto Sudibyakto; Emilya Nurjani (Faculty of Geography, Universitas Gadjah Mada, 2018)
Geographically, Indonesia has been subjected towards various climate change related phenomena. This research aim at evaluation of participatory implementation towards climate change related policy which has been set in Indonesia. The research method derived from qualitative framework developed by UNESCO. The research took RAN-API or National Action Plan upon Climate Change Adaptation which has been established since 2013. The document has been integrated within National Medium Term Plan launched at 2015 up to 2019. The research revealed that participation has been inclusive to many stakeholder involved within climate change adaptation program. Furthermore, encouragement needs to be carried out at all level especially in urbanized area. Local to national government has pivotal role to introduce many activities engaged to climate change adaptation. At different array, the research also revealed that many participation has been initiated independently by non-government organization as well as local stakeholder which need to be documented in order to ensure its merits.